The mediating roles of critical psychological factors towards the relationship between job characteristics and job outcomes: a conceptual framework / Emi Normalina Omar ...[et al.] - Omar, Emi Normalina; Rochin Demong, Nur Atiqah; Abu Hassan, Lailatul Faizah; Hassan, Narehan; Alwi, Anisah (Universiti Teknologi MARA, Kedah, 2022)
The study aims to propose a conceptual framework that investigates if job characteristics (skill variety, task identity, task significance, autonomy and feedback) will influence job outcomes of employees. It will also examine the mediating effects of psychological factors (experienced meaningfully, experienced responsibility and knowledge of results) towards that relationship. Positive psychological states are associated with work motivation, growth satisfaction, general satisfaction, and work effectiveness. Besides, critical psychological states (experienced meaningfully, experienced responsibility, knowledge of results) are included as the moderating variable. The job characteristics (skill variety, task identity, task significance, autonomy and feedback) influence the employees' job outcomes. A large body of research provides evidence that the way jobs are designed impacted the results of workers (e.g. job satisfaction) and employers (e.g. productivity). Jobs can be redesigned to increase work efficiency, minimise physical strain, and motivate the employees. A set of core job characteristics influences affective and motivational outcomes. This study used a combination of the established framework by Hackman et al. (1975,1976, 1980) and Fried & Ferris; Hogan & Martel (1987) to propose the conceptual framework. The outcomes of this research help to produce.